Develop Techniques to Retrieve Lost Data - G Reddy Sudharsan; Sunkara Munikumar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Since data plays a big role in many fields now, losing important details can have consequences for people and companies alike. It is commonly known as "Develop Techniques to Retrieve Lost data," and its goal is to establish reliable methods to stop data loss and recover what was lost. There are only User and Admin modules in the system. The User module handles user registration, accessing a project with secure login, adding files and examining one or all files uploaded in a project. People can also check and manage previous data requests, see the associated responses, restore accidentally deleted files and retrieve lost data for full control of what they keep. Features added to modern Admin include admin login, handling users and roles, monitoring files and providing support for data retrieval requests. By mixing these results, we make sure users can manage and recover their data smoothly and without trouble. This approach ensures data is kept safe and easily available which helps quickly address the major challenge of retrieving data effectively in our time. You should plan for tasks relating to data retrieval, file administration, user control, recovering lost files, data security, digital data, managing data, data recovery, modules involved, and the admin module.